Exploring pre-service English teachers digital competence in creating interactive instructional materials - Effendi Limbong; Ben Wadham (Studies in English Language and Education, 2024)
The Digital Competence of Educators (DigCompEdu) is critical in 21st-century education, which helps educators teach digital literacy to students. However, published empirical evidence regarding pre-service English teachers competence in creating interactive instructional materials with specific software applications remains scarce. This paper is grounded on the implementation of digital instructional courses at an Indonesian state university, aiming at developing pre-service EFL teachers digital competencies in designing interactive instructional materials using PowerPoint, Audacity, CapCut, Inknoe ClassPoint, Filmora, the Internet, and Canva (hereafter PACIFIC). The paper describes the pre-service English teachers self-reported abilities and challenges they encountered in designing the PACIFIC-based interactive teaching materials after completing these courses. Guided by the DigCompEdu framework, the primary data from six focus group interviews with a total number of 30 participants were analyzed by using thematic analysis. The study indicates that pre-service EFL teachers reported an adequate level of competencies in designing digital interactive instructional materials in four aspects of the DigCompEdu framework. They also reported several challenges encountered while creating the teaching materials, which mostly related to resources, such as internet connectivity and subscription access to the PACIFIC software. These findings highlight the critical need for better resource allocation and support to improve pre-service EFL teachers digital literacy and performance in designing digital teaching materials.